Frequency of Urinary Tract Infection in Postmenopausal Women (Medical Forum Monthly, 2024)
Objective: To determine the frequency of urinary tract infection in postmenopausal women visiting Bakhtawar Amin Hospital Multan.Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Department of Gynecology, Bakhtawar Amin Hospital Multan from August, 2016 to July 2017.Materials and Methods: A sample of 142 consecutive patient fulfilling the inclusion and exclusion criteria were included in the study. Informed written consent was taken from all patients. The demographic information like name, age, gender and address was noted. A detailed history and physical examination was carried out especially about symptoms of urinary tract infection. Complete urine examination was done in all the patients and 8 or more pus cells on urinary examination were considered as diagnostic of urinary tract infection. All the collected data was entered in a specially designed profroma. Results: There were 142 patients in total. Mean age of the patients was 55.92 2.88 years. Mean for parity was 3.37 1.98. There were 136/142 (95.8%) married while 6/142 (4.2%) were unmarried. Urinary tract infection was found to be present in 39/142 (27.5%). When the effect of age was noted on the frequency of urinary tract infection it was found that among patients in age group 55 years urinary tract infection was found to be present in 17/57 (29.8%) while in age group 55 years there were 22/85 (25.9%) patients with urinary tract infection (p-value = 0.702). When the effect of parity was seen on the frequency of urinary tract infection it was found that there were 6/16 (37.5%) in nulliparous group with urinary tract infection as compared to 19/58 (32.8%) in those with parity 1-3 and 14/68 (20.6%) in those with parity > 3 (p-value = 0.198) When the effect of marital status was seen it was found that among unmarried women 2/6 (33.34%) had urinary tract infection while among married women 37/136 (27.21%) had urinary tract infection (p-value = 0.742).Conclusion: Urinary tract infection has a high frequency among postmenopausal women with lower urinary tract symptoms and should be closely looked for and managed meticulously with proper antibiotics as well as by the proper implementation and utilization of preventive measures.